Extracting leading economic indicators for the Philippine economy using dynamic factor models - Simbulan, Maria Christina S... (2011)
Abstract (This paper presents a Dynamic Factor Model (DFM) approach to extracting Leading Economic Indicators developed by Stock and Watson 1991. DFM is applied to a vast member of financial and economic monthly data from January 2000 to December 2009. Three scenerios (models) were considered in the study, 1 DFM utilizing 31 indicators resulted from Principal Component Analysis applied to the entire data. The three models were evaluated vis-a-vis each other and the currently used LEIS. The results show that DFM is an effective methodology in extracting Leading Economic Indicators. DFM 31 VAR dominates the other models including the current LEIS by successfully predicting 80% correct turning points (from 2000-2009) of GDP compared to 69% of the current LEIS).
Thesis (M.A. Statistics)--University of the Philippines, Diliman.
Keywords: Economic conditions -- Philippines; Expenditures, Public -- Philippines; Gross domestic product -- Philippines; Principal components analysis